A study on the profile of the turbulence length scale in the near-neutral atmospheric boundary for sea (homogeneous) and hilly land (inhomogeneous) fetches. Issue 168 (September 2017) - Li, S.W.; Hu, Z.Z.; Chan, P.W.; Hu, Gang
Abstract: In the present study, the spatial correlation coefficients of wind speeds at different heights in the atmospheric boundary layer under near-neutral conditions are calculated based on field measurements taken by Doppler SODARs. To guarantee near-neutral stability, only measurements associated with relatively high wind strength (wind speeds in the lower boundary layer > 10 m / s ) are used in the calculation. The correlation coefficients calculated from measured data are fitted to those predicted by models to derive a vertical integral length scale. Through investigating the vertical variations of the vertical integral length scale, which is essentially the mixing length, it has been found that (a) the mixing length increases linearly with heights below 70 m, which agrees with the predictions from traditional models; (b) traditional models are applicable for predicting the vertical variation of mixing lengths in a near homogeneous sea-fetch wind flow; and (c) mean wind flow stretches the energy-containing eddy to produce larger mixing lengths, and this stretching effect is more prominent in a land-fetch flow. Highlights: Variations in correlation coefficients with distance in the vertical direction presented. Two models that depict the variations of spatial correlation coefficients with distances developed. Turbulence length scales calculated based on field measurements employed to investigate mixing length modeling. Influence from oncoming wind fetches and wind strength on mixing lengths in the near-neutral boundary layer illustrated.